Synthesis and monitored selection of nucleotide surrogates for binding T:A base pairs in homopurine–homopyrimidine DNA triple helices - Mokhir, Andriy A. (Oxford University Press, 2001)
A total of 16 oligodeoxyribonucleotides of general sequence 5′-TCTTCTZTCTTTCT-3′, where Z denotes an N-acyl-N-(2-hydroxyethyl)glycine residue, were prepared via solid phase synthesis. The ability of these oligonucleotides to form triplexes with the duplex 5′-AGAAGATAGAAAGA-HEG-TCTTTCTATCTTCT-3′, where HEG is a hexaethylene glycol linker, was tested. In these triplexes, an ‘interrupting’ T:A base pair faces the Z residue in the third strand. Among the acyl moieties of Z tested, an anthraquinone carboxylic acid residue linked via a glycinyl group gave the most stable triplex, whose UV melting point was 8.4°C higher than that of the triplex with 5′-TCTTCTGTCTTTCT-3′ as the third strand. The results from exploratory nuclease selection experiments suggest that a combinatorial search for strands capable of recognizing mixed sequences by triple helix formation is feasible.